Air Pollution from Industrial Swine Operations and Blood Pressure of Neighboring Residents - Wing, Steve (National Institute of Environmental Health Sciences, 2012)
Background: Industrial swine operations emit odorant chemicals including ammonia, hydrogen sulfide (H(2)S), and volatile organic compounds. Malodor and pollutant concentrations have been associated with self-reported stress and altered mood in prior studies. Objectives: We conducted a repeated-measures study of air pollution, stress, and blood pressure in neighbors of swine operations. Methods: For approximately 2 weeks, 101 nonsmoking adult volunteers living near industrial swine operations in 16 neighborhoods in eastern North Carolina sat outdoors for 10 min twice daily at preselected times. Afterward, they reported levels of hog odor on a 9-point scale and measured their blood pressure twice using an automated oscillometric device. During the same 2- to 3-week period, we measured ambient levels of H(2)S and PM(10) at a central location in each neighborhood. Associations between systolic and diastolic blood pressure (SBP and DBP, respectively) and pollutant measures were estimated using fixed-effects (conditional) linear regression with adjustment for time of day. Results: PM(10) showed little association with blood pressure. DBP [β (SE)] increased 0.23 (0.08) mmHg per unit of reported hog odor during the 10 min outdoors and 0.12 (0.08) mmHg per 1-ppb increase of H(2)S concentration in the same hour. SBP increased 0.10 (0.12) mmHg per odor unit and 0.29 (0.12) mmHg per 1-ppb increase of H(2)S in the same hour. Reported stress was strongly associated with BP; adjustment for stress reduced the odor–DBP association, but the H(2)S–SBP association changed little. Conclusions: Like noise and other repetitive environmental stressors, malodors may be associated with acute blood pressure increases that could contribute to development of chronic hypertension.